Penyebab dan Manajemen Konflik: Sebuah Tinjauan Literatur pada Studi Sosial, Pendidikan dan Sastra - Sofyan Sauri; Cahya Sukma Kamila; Ika Septi Wulandari; Iqbal Alfan Ni’amullah; Mualimin Mualimin (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Conflict is a universal phenomenon that affects various spheres of life, ranging from interpersonal relationships and educational organizations to socio-political dynamics. The complexity of its causes and impacts requires a comprehensive understanding to formulate effective resolution strategies. This study aims to systematically review the causes of conflict across different contexts while addressing two research questions: (1) What are the main factors that trigger conflict identified in academic literature between 2020–2024? and (2) How do contextual variations influence the understanding of conflict causes? The method employed is a literature review with article searches conducted via Google Scholar and Publish or Perish using the keyword “conflict causes.” From 20 open-access articles retrieved, a screening process based on topic relevance and publication year resulted in 6 articles for analysis. The synthesis reveals three main themes: (a) intrapersonal conflict, predominantly discussed in literary and psychological studies; (b) socio-economic conflicts, including land disputes and interethnic tensions; and (c) conflict management and resolution within educational institutions and organizations.